High frequency, higher power conversion through PWM switching using the third generation IGBTs - Neo, Tiong Guan. (2008)
The use of insulated gate bipolar transistor (IGBT) switch in power electronic application and power conversion process is now predominant. It combines the benefits that are obtainable from both the bipolar junction transistor (BJT) and metal-oxide-semiconductor field-effect transistor (MOSFET). The superiority of using IGBT power device in converters is investigated in this project initially. This device's features are studied and modeled using a combination of MOSFET, BJT devices and 5 dependent controlled sources. The behavior and characteristics of the IGBT switches is thus established in the macro model.